Bone apatite anisotropic structure control via designing fibrous scaffolds. Issue 23 (2nd April 2020) - Lee, Sungho; Nagata, Fukue; Kato, Katsuya; Nakano, Takayoshi
Abstract : Osteoblast alignment on the fibrous scaffolds as well as the subsequent apatite c -axis orientation increased with increasing fiber collecting speed. We successfully controlled cell alignment and apatite c -axis orientation using the designed morphology of fibrous scaffolds. Abstract : Bone tissue has an anisotropic structure, associated with the collagen fibrils' orientation and the c -axis direction of the bone apatite crystal. The bone regeneration process comprises two main phases: bone mineral density restoration (bone quantity), and subsequent recovery of bone apatite c -axis orientation (bone quality). Bone quality is the determinant factor for mechanical properties of bone. Control of osteoblast alignment is one of the strategies for reconstructing bone quality since the collagen/apatite matrix orientation in calcified tissues is dependent on the osteoblast orientation. In this work, fibrous scaffolds designed for reconstruction of bone quality via cell alignment control was investigated. The fibrous scaffolds were fabricated using the electrospinning method with poly(lactic acid) at various fiber collecting speeds. The degree of fiber alignment in the prepared fibrous scaffolds increased with increasing fiber collecting speed, indicating that the fibers were oriented in a single direction. The alignment of osteoblasts on the fibrous scaffolds as well as the subsequent apatite c -axis orientation increased with increasing fiber collecting speed. We successfully controlled cell alignment and apatite c -axis orientation using the designed morphology of fibrous scaffolds. To the best of our knowledge, this is the first report demonstrating that adjusting the degree of fiber orientation for fibrous scaffolds can manipulate the regeneration of bone quality.